Attributes and Magnitude of the Socio-Environmental Impacts in Environmental Impact Study and Environmental Impact Report (EIS/EIR) of two small Hydroelectric Power Plants - Demarco, Carolina Faccio; Afonso, Thays França; Ribeiro, Patricia Damasceno; Caballero, Cassia Brocca; Andreazza, Robson; Siqueira, Tirzah Moreira (Ciência e Natura, 2020)
Both SHPs selected for this study SHP Cabuí (southeast of Minas Gerais state) and SHP Caiçara (northern Minas Gerais state) are located in low-income regions. This study aimed to evaluate the approach used to describe the socio-environmental impacts - through the analysis of attributes and magnitude of impacts - of these two projects and for this, consultations were carried out on the Environmental Impact Studies (EIS) presented by these SHPs, as well as the technical opinions available on the website of the agency responsible for environmental licensing (IBAMA). It was verified that the socio-environmental approaches of the SHPs differed in some aspects. PCH Cabuí, whose previous license was deferred, used more attributes to describe the socioeconomic impacts and the explanation of the impact assessment was more detailed and easy to understand, while the EIS of the Caiçara SHP (previous license rejected) was more succinct in its attributes for the description of the socioeconomic impacts, not adequately presenting the valuation and meaning of its impacts. There is also evidence of the need to improve public participation in both projects.